2008
DOI: 10.1177/152692480801800210
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Antegrade Cardioplegia: Isolated Heart Preservation with the Asporto Heart Preservation Device

Abstract: Intermittent perfusion maintains a significantly higher myocardial pH than does a conventional single antegrade dose. This difference may translate into an improved quality of donor hearts procured for transplantation, allowing longer distance procurement, tissue matching, improved outcomes for transplant recipients, and ideally a decrease in transplant-related costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Intermittent perfusion may improve the quality of donor hearts by reducing ischemic hypoxia and cellular injury by preventing the rapid decrease in pH associated with cardiomyocyte damage. 28 In the current study, intermittent perfusion with Celsior solution supplemented with 30 μM diazoxide, an ATP-sensitive potassium channel opener, was applied as it was previously reported to confer excellent protection to the myocardium. 23 Specifically, greater myocardial oxygen consumption and glucose utilization were observed with Celsior perfusion solution, suggesting that it maintains greater metabolism during storage and thereby increased cardiac function and myocyte survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermittent perfusion may improve the quality of donor hearts by reducing ischemic hypoxia and cellular injury by preventing the rapid decrease in pH associated with cardiomyocyte damage. 28 In the current study, intermittent perfusion with Celsior solution supplemented with 30 μM diazoxide, an ATP-sensitive potassium channel opener, was applied as it was previously reported to confer excellent protection to the myocardium. 23 Specifically, greater myocardial oxygen consumption and glucose utilization were observed with Celsior perfusion solution, suggesting that it maintains greater metabolism during storage and thereby increased cardiac function and myocyte survival.…”
Section: Discussionmentioning
confidence: 99%
“…9 Alternatively, heart preservation using continuous perfusion can provide the energy required for metabolism during cold ischemic heart preservation, remove the acidic metabolites, and prolong the time of donor heart preservation by 8-10 h. 10,11 However, continuous perfusion has several shortcomings, such as inducing tissue edema, increased vascular edema, and increased endothelial injury, in addition to the requirement of a special perfusion device and large volumes of preservation solution because of the elongated preservation time, 12-14 some of which cannot be overcome even with retrograde perfusion. 15 Therefore, intermittent perfusion at low temperature may be more advantageous than continuous perfusion 16 as it not only provides metabolic substrates and rinses metabolites as with continuous perfusion but also reduces the total volume of perfusion solution required and decreases the myocardial edema and vascular endothelial injury. However, because both continuous perfusion 15 and intermittent perfusion are affected by perfusion pressure, velocity, and time, [17][18][19] further studies are necessary to identify the parameters for optimal myocardial protection to prevent endothelial cell and smooth muscle cell damage, resulting in increased capillary permeability and release of vasoactive substances and subsequent vasospasm, insufficient microvascular perfusion, and cardiac dysfunction soon after transplantation as well as long-term outcomes (e.g., chronic cardiac allograft vasculopathy).…”
mentioning
confidence: 99%
“…Physiologically, the endothelial cell swelling affects myocardial perfusion likely from a reduction in capillary diameter. Supporting this concept, a study by Rivard et al (13) showed that prolonged hypothermic storage causes a significant decrease in microvascular perfusion occurring in the acidotic donor heart.…”
Section: Review Articlementioning
confidence: 94%
“…The LifeCradle uses a thermoelectric Peltier type device to maintain hypothermia, whereas the LifePort uses ice as the cooling medium. Rivard et al (13) have used a simple portable approach (Asporto) without oxygenation using intermittently pumped non-recirculated cardioplegia, also cooled with a Peltier device.…”
Section: Donor Heart Preservation Techniquesmentioning
confidence: 99%
“…Beyond the obvious priority for cannulating within the warm ischemia limits of a DCD, there are often simple and straightforward opportunities for shaving off minutes of ischemic time such as an expedited departure from the donor hospital, meticulous coordination with the air and ground transport teams, and selection of the optimal transport strategy. Operational efficiency in transporting the donor, although often overlooked, represents the primary focus of a growing number of ventures which were recently formed to address this problem 11–14 . Perhaps with the regulatory approval of drone delivery, surgeons will once again enjoy the benefits of performing the pulmonary arterial anastomosis on an arrested heart.…”
Section: Figurementioning
confidence: 99%